2022
DOI: 10.1002/pld3.407
|View full text |Cite
|
Sign up to set email alerts
|

Maize resistance to insect herbivory is enhanced by silencing expression of genes for jasmonate‐isoleucine degradation using sugarcane mosaic virus

Abstract: Previously, sugarcane mosaic virus (SCMV) was developed as a vector for transient expression of heterologous genes in Zea mays (maize). Here, we show that SCMV can also be applied for virus-induced gene silencing (VIGS) of endogenous maize genes. Comparison of sense and antisense VIGS constructs targeting maize phytoene desaturase (PDS) showed that antisense constructs resulted in a greater reduction in gene expression. In a time course of gene expression after infection with VIGS constructs targeting PDS, les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…JA signaling can also be regulated through metabolism of JA-Ile via 12-hydroxylation and subsequent hydrolysis and silencing of genes pertinent to this reaction have been already shown to have consequences for resistance to FAW (Chung et al 2022). In our study, the amounts of 12-hydroxy JA and 12-hydroxy JA-Ile were higher after 24 hours of rice versus corn strain herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…JA signaling can also be regulated through metabolism of JA-Ile via 12-hydroxylation and subsequent hydrolysis and silencing of genes pertinent to this reaction have been already shown to have consequences for resistance to FAW (Chung et al 2022). In our study, the amounts of 12-hydroxy JA and 12-hydroxy JA-Ile were higher after 24 hours of rice versus corn strain herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression in maize has been demonstrated via insertion of cloning sites that allow these viruses to express proteins from sequences that are cloned in frame with the viral polyprotein (Mei et al, 2019 ; Tatineni et al, 2010 ; Xie et al, 2021 ). Interestingly, gene fragments for VIGS applications can also be inserted into these positions as long as the open reading frame (ORF) is preserved (Chung et al, 2022 ; Xie et al, 2021 ). Moreover, it was shown that MDMV can be used to simultaneously express a protein and silence multiple target genes in maize plants (Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several virus vectors have been used for VIGS in monocot plant species, including Chinese wheat mosaic virus ( Yang et al, 2018 ), tobacco rattle virus (TRV) ( Zhong et al, 2014 ), barley stripe mosaic virus ( Buhrow et al, 2016 ), brome mosaic virus ( Wang et al, 2021 ), bamboo mosaic virus, cymbidium mosaic virus ( Hsieh et al, 2013 ), rice tungro bacilliform virus ( Purkayastha et al, 2010 ), cucumber mosaic virus ( Tzean et al, 2019 ), foxtail mosaic virus ( Liu et al, 2016 ), maize rayado fino virus ( Mlotshwa et al, 2020 ), and sugarcane mosaic virus (SCMV) ( Mei et al, 2019 ; Chung et al, 2022 ). Several of these viruses, including SCMV, have been used for VIGS in maize ( Mei et al, 2016 ; Wang et al, 2016 ; J. Zhang et al, 2017 ; Ding et al, 2018 ; Jarugula et al, 2018 ; Mlotshwa et al, 2020 ; Chung et al, 2022 )…”
Section: Introductionmentioning
confidence: 99%
“…SCMV is a positive strand RNA virus of the Potyviridae family that infects many monocots including sugarcane, maize, wheat, and sorghum ( Xiao et al, 1993 ). Previously, SCMV has been used as a vector for transient overexpression of non-maize genes ( Mei et al, 2019 ), overexpression of maize endogenous genes ( Chung et al, 2021 ), VIGS of maize endogenous genes ( Chung et al, 2022 ), and plant-mediated VIGS of gene expression in corn leaf aphids ( Rhopalosiphum maidis ) feeding on maize ( Chung and Jander, 2022 ). The plasmid vector pSCMV-CS3 ( Mei et al, 2019 ; Chung et al, 2022 ) allows for both efficient gene overexpression and gene expression silencing by RNA interference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation